THE REPRESENTATION OF IDENTITY IN THE PRACTICES OF VIRTUAL COMMUNICATION - A. A. Lisenkova (Концепт: философия, религия, культура, 2019)
The article analyzes the current state of virtual communication social space as a specific field of construction and representation of identification strategies. The peculiarity of this process is not only inherent in all virtual communications interactivity, anonymity, globality and constant involvement, but also in the emergence of new areas of so-called professional Amateur, stimulating the development of additional skills in various fields. These changes are the basis for transformation identification of policies and practices in the environment of virtual communication, presenting new requirements for 4K competencies of the modern person and creating conditions for the development of avtoproekt identities with virtual publicity capital in the space of the global network, subsequently exerting enormous influence on the actual everyday practices of identification and representation in connection with a smaller separate online and offline space.Contemporary global socio-cultural virtual space "is formed from collapsing blocks of text culture, konstruirujas on the principle of montage or collage. However, the cognitive subject aims to recreate the integrity culture, give her some, let loose and loose, but the form "[Sayapin, 2012:109]. This form gives a new reason for identification strategies, manifested in creative designing interactive content on the basis of a real personal experience. Virtual practice amateurishness, therefore, have a significant impact not only on identification processes, but also in the field of culture in General, while on par with professional in the field of a single media space, getting feedback, recognition and the possibility of personal realization and identification in new spheres.